An Alternative Long‐Term Culture System for Highly‐Pure Mouse Spermatogonial Stem Cells. Issue 6 (June 2015) - He, Bao‐Rong; Lu, Fan; Zhang, Lingling; Hao, Ding‐Jun; Yang, Hao
<x xml:space="preserve">Abstract</x> Increasing evidence suggests that spermatogonial stem cells (SSCs) have great clinical potential to give rise to a variety of cell types besides all spermatogenic lineage cells. The development of an efficient method for long‐term culture of highly‐pure SSCs is essential for further studies related to SSC biological events. Here, we describe an in vitro culture system obtaining mouse SSC cultures of high purity, viability, and proliferation. For establishing long‐term cultures of SSCs, we mainly focused on isolation procedures and culture conditions. These included co‐coating of extracellular substrates, that is, poly‐L‐lysine (PLL) and laminin, as well as combinatiorial use of three milder enzymes and simultaneously less trypsin to minimize enzyme‐mediated degradation of SSCs. Furthermore, a unique purification procedure was performed to effectively eliminate contaminating non‐SSCs. Finally, a critical step is to ensure SSC maintenance and expansion by utilizing optimal culture medium. Obtained data suggest that applying our optimally modified method, SSCs can be cultured for over 90 days with high purity (around 93.5%). Moreover, SSCs isolated and expanded using our protocol fulfills all criteria of SSCs without losing their stemness‐characterized by SSC‐phenotypic gene expression and long‐term self‐renewal. This study describes for the first time a protocol allowing isolation and expansion of SSCs suitable for numerous studies related to SSC‐based clinical therapies of various diseases. J. Cell. Physiol. 230: 1365–1375, 2015. © 2014 Wiley Periodicals, Inc., A Wiley Company